2023
DOI: 10.1021/acs.jafc.3c02339
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Characterization of Bovine Myocardium Hydrolysates and Its Ameliorative Effects on Doxorubicin-Induced Myocardial Injury in H9c2 Cells and in Mice

Wen Li,
Miao Lv,
Tiantian Zhang
et al.

Abstract: The prevalence and mortality of heart disease have a persistent existence, and it is important to develop active substances with cardioprotective properties. It has been reported that peptides from animal heart hydrolysates possess cardioprotective activity, but those mechanisms and the sequence of peptides are still unrevealed. In the present study, the extracts of bovine myocardium were prepared by enzymatic hydrolysis (BHH-A) and water extraction (BHH-W). The cardioprotective function of peptides was verifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Therefore, it is necessary to take corresponding methods to improve its bioavailability and efficacy. Previous studies have shown that proteins can be well absorbed by cells after being hydrolyzed into peptides or amino acids by enzymes, thus improving their bioavailability and efficacy ( Li et al, 2023 ; Xu et al, 2023 ). Several bioactive peptides and proteins have been reported from the in-depth studies on leeches.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to take corresponding methods to improve its bioavailability and efficacy. Previous studies have shown that proteins can be well absorbed by cells after being hydrolyzed into peptides or amino acids by enzymes, thus improving their bioavailability and efficacy ( Li et al, 2023 ; Xu et al, 2023 ). Several bioactive peptides and proteins have been reported from the in-depth studies on leeches.…”
Section: Introductionmentioning
confidence: 99%